"Non-metabolizable" glucose analogue shines new light on priming mechanisms: Triggering of microbial metabolism. (April 2017) - Mason-Jones, Kyle; Kuzyakov, Yakov
Abstract: Priming of soil organic matter decomposition has attracted much research interest, yet a conclusive mechanistic explanation of the phenomenon remains elusive. One proposal is that low molecular weight organic substances might "trigger" an acceleration of microbial metabolism. For the first time, we applied a glucose analogue to soil to demonstrate triggering of microbial metabolism, and to estimate its relative contribution to priming. "Non-metabolizable" glucose analogues have been widely used in pure culture studies to mimic glucose, but never in soil biochemistry. We hypothesized that analogue molecules will elicit a metabolic response in microorganisms despite limited catabolism, and thereby confirm the proposed triggering. The effect of 14 C-labeled 3- O -methyl-d -glucose (OMG) – a common "non-metabolizable" glucose analogue – on soil organic matter mineralization was compared to that of 14 C-labeledd -glucose. OMG was mineralized, but its mineralization was initially impeded and substantially delayed, relative to glucose. OMG caused brief but strong priming in the first 24 h, increasing unlabeled CO2 efflux by 173%, 89% and 36% above control for additions of 0.49, 2.4 and 4.9 μmol OMG g −1 soil, respectively. In contrast, glucose caused low or negative priming on the first day. On the first day after OMG addition, a negative correlation between priming and OMG mineralization indicated that triggering is a valid mechanism of microbial activation during a famine-feast transition, but is short-lived. Glucose mineralization peaked on the second day for medium and high additions, coinciding with peaks in positive priming. Maximum substrate mineralization also coincided with peaks in priming for medium and high OMG levels, but these occurred 9 and 11 days after addition, respectively. This revealed non-triggering priming mechanisms, which contributed most to priming and were closely coupled to substrate mineralization. By separating energy- and substrate-dependent metabolic processes from triggering processes, the glucose analogue 3- O -methyl-d -glucose enabled triggering to be demonstrated, but triggering by glucose occurs without contributing greatly to priming. Graphical abstract: Highlights: Analogue 3- O -methylglucose (OMG) mineralization impeded and delayed compared to glucose. OMG induced more priming than glucose shortly after addition, confirming triggering. Non-triggering mechanisms contributed the most to priming effects. Priming and substrate mineralization rates were closely positively correlated.